Correlation of Fatigue with Clinical Parameters and Quality of Life in Rheumatoid Arthritis - Yasemin Turan,; Zehra Kocaağa,; Hikmet Koçyiğit,; Alev Gürgan,; Korhan Barış Bayram,; Serdar İpek, (Archives of Rheumatology, 2010)
Objective: We aimed to investigate fatigue and its relationship with disease activity, radiological findings and quality of life in patients with rheumatoid arthritis (RA). Materials and Methods: 41 patients who were diagnosed as RA according to criteria of ACR and 38 healthy controls were enrolled to this study. Patients were asked to record the severity of rest pain (Visual Analog Scale) and duration of morning stiffness. Fatigue was evaluated by the Multidimensional Assessment of Fatigue (MAF) test. Disease activity and quality of life were assessed respectively with DAS-28 and Short Form-36 (SF-36). Radiologic involvement was evaluated according to modified Larsen's grading system. Results: The mean age of patient and control groups were 50.9±13.4 years and 50±10.1 years, respectively. Two groups were similar with respect age (p=0.744). The median MAF total score was higher in patients with RA (38.5, min-max: 4-50) than in control subjects (22.5, min-max: 0-42) (p<0.001). There were significant correlations between MAF and DAS-28 scores (r=0.478, p=0.004), rest pain (r=0.491, p=0.001), ACR functional scale (r=0.563, p<0.001) and four dimensions of SF36; physical role (r=-0.504, p=0.014), bodily pain (r=-0.416, p=0.048), vitality (r=-0.522, p=0.011), emotional role (r=-0.523, p=0.011). Conclusion: Fatigue symptom may be quite disabling for patients with rheumatoid arthritis. It is affected by disease activity and pain but not by disease duration and radiologic score. Therefore, it is concluded that fatigue is essentially related with disease activity rather than the chronic inflammatory process in RA. (Turk J Rheumatol 2010; 25: 63-7)